Studi Prevalensi Penggunaan Alat dan Obat Kontrasepsi di Masyarakat Kabupaten Bandung - Weking, J. M.; Sutrisno, Entries; Kamilla, Gladdis (Jurnal Farmasi Indonesia, 2015)
Governmentâ??s efforts in controlling the populationâ??s family planning program (KB) is using contraception. Contraception is a devices or a drug that is used to prevent conception (pregnancy). The purpose of this study was to determine the prevalence use of contraceptive drugs and devices (Alokon) in the community of Bandung Regency in July-August of 2013. This research uses the observation method with the cross sectional eksional questionnaire contain- ing questions related to knowledge, attitudes, and behaviors of 290 respondents about the use of Alokon. Results of the study showed that 87% of respondents know the Government program in terms of the number of children is recommended (two children). Respondents understand Alokon as a means of pregnancy prevention (78%) and can be used as requirements (42%). This type of contraception is the most known and used by the respondents are: Implants (5%), IUD (19%), birth control pills (20%) and injection (23%). In addition, respondents believed that it is not effective to delay pregnancy (82%). The existence of the respondentâ??s concern with respect to side effects(56%), Alokon among others obesity(42%). Alokon used more by women (75%) than men (4%). Alokon more chosen (43%) compared to devices (19%). Based on the results of the study it can be concluded that the respondents have a good knowledge in terms of Alokon and its use. Considering the type of medication Alokon (birth control pills) are chosen by many respondents, the required role of pharmacists in pharmaceutical care in giving right information about how to use to achieve their effectiveness as contraceptives (prevention of pregnancy).